Portugal : Financial Sector Assessment Program; Technical Note; Investor Protection, Disclosure, and Financial Literacy. (IMF Staff Country Reports; Country Report ;, 2007)
This technical note on Investor Protection, Disclosure, and Financial Literacy for Portugal explains investor protection and corporate governance. Comissao do Mercado de Valores Mobiliarios (CMVM) is the regulator in charge on ensuring compliance with disclosure issues as well as the corporate governance framework. It has also participated in the creation of a specialized program in securities at the university level. Portugal has implemented an investor compensation scheme, which covers securities and money in relation to client investment operations with a limit of Euro 25.00 per investor.